ECONOMIC EMPOWERMENT OF RURAL COMMUNITIES THROUGH THE ROLE OF THE ARGOPURO VILLAGE COOPERATIVE IN KRUCIL DISTRICT, PROBOLINGGO REGENCY. - Riska Wardatul Jannah; Siti Aisyah; Ridho, Zainur; Nuriawati (International Journal of Multidisciplinary Reseach, 2025)
This study aims to evaluate the role of the Argopuro Village Cooperative (KUD) in empowering the economy of the community in Krucil District. KUD Argopuro is known to be active in various economic and social activities in the region. This study uses a qualitative descriptive method with a case study approach. Data was collected through in-depth interviews with cooperative managers, members, and local residents, as well as through direct observation and document analysis. The research findings indicate that KUD Argopuro plays a significant role in improving the economic well-being of the Krucil community. The cooperative provides services such as savings and loans, agricultural supply provision, and skill training for members and the general public. The savings and loan program helps the community access business capital at low interest rates, while the provision of agricultural supplies supports farmers in improving productivity and crop quality. Additionally, the skills training provided by the cooperative has helped the community develop small and medium-sized businesses. KUD Argopuro has a positive impact on the economic empowerment of the Krucil community. However, there are still challenges that need to be addressed, such as improving cooperative management and expanding market access for local products. The research recommendations include enhancing the capacity of cooperative managers, diversifying products and services, and strengthening partnerships with external parties.